Disconfirmation as a Mediator of Expectation and Performance Effects on UHC Satisfaction in Sampang Regency - Sindi Ayu Antika; Bagus Nuari Harmawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The Sampang Regency Government has implemented the Universal Health Coverage (UHC) program, which means that all levels of society will receive quality health services without considering finances. However, in its implementation, there are still budgetary problems so that the government deactivated 38,990 UHC participants. The purpose of this study is to examine the influence of expectations, performance, and disconfirmation on the level of public satisfaction as recipients of UHC services at the Sampang Regency Regional Hospital using the Expectancy Disconfirmation Model from Van Ryzin (2004). This study uses a quantitative approach with an explanatory research type and a survey research strategy. The study population is inpatients at the Sampang Regency Regional Hospital in 2024. To determine the number of samples, the Isaac and Michael formula was used with a sampling technique, namely simple random sampling. The instrument used was a questionnaire. The data analysis and interpretation technique in this study uses path analysis. In addition, correlation and multiple regression are used as the basis for calculating the path coefficient. The results of this study indicate that the level of expectations and performance influences disconfirmation by 0.478, and the level of expectations, performance, and disconfirmation influences the level of citizen satisfaction by 0.678. From the results of this study, it shows that the expectation disconfirmation model is very appropriate for the public sector because it can determine how to manage public satisfaction.